Potential and Mitigation Analysis of Nipah Beach Forest Ecosystem Changes, North Lombok Regency as a Sea Turtle Habitat - Syaputra, Maiser; Wahyuningsih, Endah; Suparyana, Pande Komang; Permatasari, Diah; Lestari, Andi Tri (Jurnal Multidisiplin Madani, 2023)
The Nipah beach forest in Malaka Village is used as a nesting habitat for sea turtles, which are protected and endangered wild animals in Indonesia. In current conditions, the Nipah Beach forest ecosystem is faced with development, economic growth, and the community's high demand for land so the integrity of the turtle habitat in the area is threatened. Analysis of potential changes in wildlife habitat is important to carry out at Nipah Beach, Malaka Village, and is interrelated with efforts to prepare plans and strategies for handling and protecting turtle biodiversity itself. This research aims to 1). Knowing the characteristics of turtle diversity in the Nipah Beach forest area, North Lombok Regency. 2). Changes potential analyzing for Nipah Beach forest ecosystem, North Lombok Regency as a sea turtle habitat. 3). Develop a mitigation plan for changes in the Nipah Beach forest ecosystem, North Lombok Regency as a sea turtle habitat. Measuring sea turtle diversity was carried out using the observation method, while risk analysis of habitat change in this study was carried out using risk analysis techniques using SNI/ISO 31010, and mitigation plans were prepared using the Mitigation Hierarchy. The results obtained were analyzed using risk analysis based on AS/NZS Australian/New Zealand Risk Management Standard 4360 (2004). The conclusions of this research are: 1). Sea turtle diversity on Nipah Beach consists of three species, namely the Hawksbill turtle (Eretmochelys imbricata), Green turtle (Chelonia mydas), and Olive ridley turtle (Lepidochelys Olivacea). The important habitat for turtles on Nipah Beach is at stations 2, 3 and 5. 2). Potential changes to the Nipah Beach forest ecosystem are divided into five degrees of change, from mild to disaster. The highest degree of change occurs if the important nesting habitat of the Hawksbill turtle (Critical Endangered IUCN) is disturbed/lost on a large scale. 3). Mitigation steps in protecting the Nipah Beach forest ecosystem for sea turtle habitat consist of avoiding, minimizing, rehabilitation and balancing